Democracy, Corruption, and Economic Decline in Nigeria: Evaluating Civilian Administration Since 2015 (Journal of Peace, Security and Democracy, 2026)
This study examined the relationship between democracy, corruption, and economic decline in Nigeria, with particular emphasis on civilian administrations since 2015. It is anchored on Public Choice Theory, which explains political behaviour as being driven primarily by self-interest rather than collective welfare. The study adopted a qualitative approach, using a historical research design and content analysis of relevant academic literature, policy documents, and documentary evidence.  Findings reveal that although Nigeria has maintained democratic governance since 2015, expected developmental outcomes have been constrained by persistent corruption and weak institutional frameworks. Corruption remains deeply embedded in public administration, manifesting through mismanagement of public resources, weak accountability systems, and political patronage. These challenges have significantly contributed to economic decline, reflected in rising unemployment, inflation, deteriorating infrastructure, and increasing public debt. The study further shows that civilian administrations have struggled to translate democratic governance into meaningful economic development due to policy inconsistency and institutional inefficiency. The study concludes that democracy in Nigeria has not delivered optimal economic outcomes due to entrenched corruption and governance weaknesses, in line with the propositions of Public Choice Theory. It recommends, among others, that anti-corruption institutions in Nigeria be strengthened through enhanced operational independence, adequate funding, and the strict enforcement of accountability mechanisms. This will help to reduce political interference, improve institutional effectiveness, and promote transparency in public administration.